Penerapan Sanksi Pidana Di Bidang Lingkungan Hidup Menurut UUPLH - Zairin Harahap (Jurnal Hukum IUS QUIA IUSTUM, 2005)
The implementation of criminal sanction committed by the corporations is not regulated clearly on the Act No. 23/1997. It does not determine definitely, who must be responsible, whether the director of the corporation orthe people who has the authority that can be threaten by prison sentence. Besides that, the sanction to individual who damages or pollutes the environment is higher than it's committed by the corporation. However, it isnecessarily to develop the Environmental Management Act.